Allergic sensitization in patients with pruritus sine materia in the absence of a somatic cause (Annals of Medical Research, 2021)
Aim: Pruritus sine materia in the absence of a somatic cause is generally attributed to psychogenic factors, but it is also well known that psychological stress may affect skin through its impacts on immune response. In this three-year retrospective study we aimed to reveal the allergic sensitization of patients with chronic pruritus without a somatic cause. Material and Methods: Three hundred and sixty five male and female patients with widespread chronic pruritus between 6 and 75 years old were retrospectively recruited. In addition to routine hematologic examination, skin prick test and serum total IgE measurement were performed on each patient.Results: In cutaneous examination, the patients had no visible manifestation except self excoriations in some, and all had normal values in hematologic laboratory examination. Altogether 10% of patients had positive results for both skin prick test and serum total IgE, and 42% of patients had positive results for either skin prick test and/or serum total IgE, which may be regarded as a presentation of immediate type hypersensitivity.Conclusion: Considering the quite high positive ratios obtained for both skin prick test and serum total IgE, it may be encouraging to perform these tests routinely on the patients with pruritus sine materia, both for revealing a probable allergic tendency and for better handling the treatment modalities.
Keywords: Pruritus sine materia; skin prick test; IgE; allergy